ANALYSIS OF MORPHOLOGICAL AND BIOCHEMICAL CHANGES IN RAT SALIVARY GLAND UNDER EFFECT OF ACUTE STRESS DEPENDING ON THE TYPE OF NERVOUS REGULATION - Tsuber, V.Y. (World of Medicine and Biology, 2012)
The present study demonstrates concurrent biochemical and pathomorphological alterations in the rat submandibular salivary gland in acute stress. The adverse changes indicate inhibition of protein synthesis caused by activation of free radical processes and decrease in protective antioxidants. The severity of the changes depends on the type of the nervous regulation. The salivary glands of stress predisposed rats are more stress-sensitive compared to stress-resistant rats.
Keywords: acute stress; reaction type; salivary glands